Records - Catholic Church. Province of Oceania; Oceania Marist Province Archives; Australian National University. Pacific Manuscripts Bureau (Suva : Oceania Marist Province Archives, 1900)
Records of the Province of Oceania containing mainly incoming letters, outgoing letters and documentation of the provincial's office and the procurator's office. The archives of this province are very incomplete.
OMPA 361 - OMPA 400.
Microfilmed for the Oceania Marist Province Archive, P.O. Box 1198, Suva, Fiji. Distributed by the Pacific Manuscripts Bureau, Canberra, A.C.T.
Microfilm copy of originals held by Oceania Marist Province Archives, 7 Lavena Road, Suva, Fiji.
The Province of Oceania is one of many provinces of the Marist Fathers (Society of Mary) throughout the world. It was formed in 1898 Oct. 28 and covers the eight Pacific dioceses or archdioceses of Wallis/Futuna, Tonga, Samoa and Tolelau, Port Vila, Noumea, Suva, Honiara and Kieta. Until 1966, these dioceses or archdioceses were called Vicariates Apostolic.
Keywords: Catholic Church. -- Province of Oceania -- Archives; Catholic Church -- Oceania